BEYOND TECHNOCRATIC GOVERNANCE: ESTABLISHING A 'MASLAHAH AUDIT' FRAMEWORK FOR CENTRALIZED PMO DIRECTIVES IN INFRASTRUCTURE MEGAPROJECTS - Wahyu Istiqo Marga Cromer; Rahmat Mulyana (Department Islamic Economics, 2026)
Megaprojects are conventionally evaluated through restrictive technocratic parameters—namely, on-time, on-budget, and within-scope metrics—frequently failing to capture long-term socio-distributive impacts and structural fiscal exposures. This study addresses this evaluative void by establishing a novel evaluation framework termed the 'Maslahah Audit,' derived from the systemic principles of Maqasid Shariah. Adopting an interpretive-constructivist lens and an instrumental case study design, we examine a multi-billion-dollar Metropolitan Light Rail Transit (MLRT) megaproject governed by a centralized PMO Directive structure. To meet rigorous international research ethics, all institutional identities and informant profiles are strictly anonymized using functional codes. Primary empirical data collected from 18 purposively selected key informants—including ministerial regulators, state-owned enterprise (SOE) executives, corporate finance heads, and Sharia scholars—were cross-examined via comprehensive documentary triangulation. Reflexive thematic analysis reveals that while the centralized PMO Directive model drives technical acceleration, its hyper-centralization introduces severe 'single-point decision-making' vulnerabilities. Furthermore, critical ethical tensions manifest in the protection of life (hifz al-nafs) regarding substantive public engagement during land acquisition, and the protection of wealth and generation (hifz al-mal and hifz al-nasl) due to persistent cost overruns and reliance on long-term state-backed debt syndications. This study argues for a paradigm shift from purely technocratic controls to values-driven governance networks, offering the 'Maslahah Audit' as a standardized diagnostic tool to ensure public investments deliver absolute holistic welfare (maslahah).